2020
DOI: 10.1126/sciimmunol.abe5511
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of serum and saliva antibody responses to SARS-CoV-2 spike antigens in COVID-19 patients

Abstract: Although the antibody response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been extensively studied in blood, relatively little is known about the antibody response in saliva and its relationship to systemic antibody levels. Here, we profiled by enzyme-linked immunosorbent assays (ELISAs) immunoglobulin G (IgG), IgA, and IgM responses to the SARS-CoV-2 spike protein (full-length trimer) and its receptor binding domain (RBD) in serum and saliva of acute and convalescent patients with lab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
515
2
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 775 publications
(611 citation statements)
references
References 53 publications
44
515
2
7
Order By: Relevance
“…Consequently, anti-SARS-CoV-2 IgG and IgM levels, which mainly transudate from the blood into the mucosa, correlate well between both compartments. In contrast, IgA was found to be more abundant in the mucosa, particularly early during disease, which supports the hypothesis that SARS-CoV-2 infection triggers local sIgA production [261,262].…”
Section: Antibody Binding and Neutralizationsupporting
confidence: 78%
“…Consequently, anti-SARS-CoV-2 IgG and IgM levels, which mainly transudate from the blood into the mucosa, correlate well between both compartments. In contrast, IgA was found to be more abundant in the mucosa, particularly early during disease, which supports the hypothesis that SARS-CoV-2 infection triggers local sIgA production [261,262].…”
Section: Antibody Binding and Neutralizationsupporting
confidence: 78%
“…Previous studies reported varying results in longitudinal changes of the virus-specific antibody response. Some detected stable antibody titers 4 to 6 months after diagnosis [1,2], while others reported waning of the antibody response 2 to 3 months after infection [3,4]. Differences in assay sensitivity and antigen targets may account for these discrepancies, with Spike and Nucleocapsid being the main antigens investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies including convalescent adults reported that humoral immunity against SARS-CoV-2 may be short-lived, particularly in persons with mild illness [3][4][5] . However recent findings provided evidences of nAbs persisting up to 6 months [6][7][8][9][10] , as after seasonal and SARS-like coronavirus infection, where nAbs can persist, respectively up to one or several years 11,12 .…”
Section: Introductionmentioning
confidence: 99%